Developing a Digital Platform for Interior and Renovation Services Using the Business Model Canvas (BMC) Approach - Lailatur Rahmi; Ferizka Tiara Devani; Laras Ayu Anastasya; Dzaky Hanifah Ahmad (Universitas Islam Kuantan Singingi, 2025)
This research was motivated by the ongoing difficulty of searching for and managing interior design and renovation services, which are typically conducted through personal recommendations and social media. This situation makes it difficult for clients to find suitable service providers, compare service quality and prices, monitor project progress, and obtain guaranteed transaction security and structured work documentation. Furthermore, interior designers and renovation contractors also experience limitations in promoting portfolios, managing projects, and building professional reputations objectively. These impacts include low efficiency in the service search process, lack of project transparency, and limited collaboration opportunities between clients and service providers. To address these issues, the web-based DesignIn platform was developed, integrating interior design and renovation services into one centralized system. Platform development began with a Business Model Canvas (BMC) analysis to generate a business model tailored to user needs. The development results indicate that DesignIn is able to facilitate the search for verified partners, project management, communication, digital contracts, progress monitoring, and an integrated payment system. Thus, this platform can improve the efficiency, transparency, security, and quality of interior design and renovation services.